Achieving Millimetre Wave Seeker Performance Evaluation Based on the Real-Time Kinematic. (24th December 2020) - Chen, Shichao; Lu, Fugang; Liu, Ming; Wei, Jingbiao; Xing, Mengdao
Abstract : The millimetre wave (MMW) seeker can realize target detection under all weather conditions, the performance of which directly determines the design of the control algorithms. To guarantee the hitting accuracy and damaging effect of the expensive MMW guidance missile, assessing the performance of the seeker is indispensable before the launching of the missile. Real tactical environment of the seeker cannot be simulated comprehensively by indoor laboratories, and high-precision evaluation method outdoor is desperately needed. Focusing on the problem, a method for outdoor MMW seeker performance evaluation is proposed via the real-time kinematic (RTK) technology in this paper, which has the advantages of high-precision orientation and working ability under all climates. Firstly, the geometry of the seeker performance evaluation system is constructed, guaranteeing the effective working of the RTK. And then, the key parameters associated with the guidance control are calculated on the basis of the global position system (GPS) measurements. Finally, comparisons are made between the parameters obtained based on the RTK and the seeker outputs. Besides, for the performance assessment of the MMW seeker towards moving targets, a time synchronization method for different GPS carrier platforms is presented. The effectiveness of the proposed method is validated by the mooring test-fly experiments. Experimental results demonstrate that the performance of the MMW seeker can be evaluated effectively by using the proposed RTK-based method.